Comparing performances of MICP bacterial vegetative cell and microencapsulated bacterial spore methods on concrete crack healing - Intarasoontron, Jirapa; Pungrasmi, Wiboonluk; Nuaklong, Peem; Jongvivatsakul, Pitcha; Likitlersuang, Suched (Construction & building materials, 2021)
•MICP self-healing concrete by dropping and immobilization methods are compared.•Vegetative cells and microencapsulated bacterial spore for MICP are investigated.•Crack-healing and load-carrying performance are evaluated on MICP-treated mortars.•Dropping method showed higher crack healing ratio and ultimate load after repair. This study compares the crack healing performances of biological self-healing concretes using cell/nutrient dropping and immobilization methods to produce microbially induced calcium carbonate precipitation (MICP). Vegetative cells and microencapsulated bacterial spores of Bacillus sphaericus (LMG 22257) were used to heal pre-cracked mortars. Mortar specimens were cured for 7 and 28 days before pre-cracking, and then repaired under wet-dry cycles for 7 days. Comparisons were made in terms of crack-width and crack-area healing and load recovery after repairing. Results showed that the vegetative cell dropping method was more effective in closing cracks and recovering ultimate load after repair than the method of using immobilized microencapsulated bacterial spores for mortar repair. In fact, specimens mixed with microencapsulated bacterial spores exhibited lower ultimate loads than comparable control specimens.